PENERAPAN MODEL PEMBELAJARAN KOOPERATIF PENDEKATAN STRUKTURAL TWO STAY TWO STRAY UNTUK MENINGKATKAN HASIL BELAJAR MATEMATIKA SISWA KELAS VIII2 SMPN 2 BANGKINANG KOTA - Nurfadila, Rafiqo; Anggraini, Rini Dian (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2016)
Abstract: The purpose of this research is to improve the learning process and to improve mathematics achievement by applying the cooperative learning model of structural approach Two Stay Two Stray. The research is classroom action research (PTK) that consist of two cycles and at the end of every cycle carried out mathematics achievement test. The subject of this research is students of class VIII2 SMPN 2 Bangkinang Kota in the second semester academic years 2014/2015, there are 29 students in the class, consist of 9 boys and 20 girls. Data collecting through observation and written test. The observation was doing for the observation of learning activity of teacher and students, of student’s attitude and of student’s skill. While written test which in daily test form was doing to evaluate student’s knowledge. Base on the result of analysis, the amount of student that reaching KKM for attitude interest improves from 65,52% at early scor and become 75,86% at the first cycle and become 100% at the second cycle. The amount of student that reaching KKM for skill interest improves from 41,38% at early scor and become 51.72% at the first cycle and become 82,76% at the second cycle. The amount of student that reaching KKM for knowledge interest improves from 55.17% at early scor and become 65,52% at the first cycle and become 89.66% at the second cycle. The result of research conclude that applying the cooperative learning model of structural approach Two Stay Two Stray can improves the learning process and improves mathematics achievement of VIII2 SMPN 2 Bangkinang Kota in the second semester academic years 2014/2015.Key words : Mathematics learning outcome, Cooperative Learning Model Structural Approach of Two Stay Two Stray, Classroom Action Research.